Informed Consent and Criminal Liability. - Obando Freire, Francisco; Medina Cuenca, Arnel (Conexiones UG, 2025)
Background: Advances in Science and Technology within Health Sciences inherently bring an increase in risks associated with medical interventions. To ensure the patient is aware of the probabilities of adverse events, the informed consent document is presented. Objective: To provide a legal basis for the juridical premises that sustain informed consent and the concomitant criminal liability for medical malpractice. Methods: Doctrinal legal systematization of objective imputation, objective duty of care, and informed consent. Results: Communication with patients via informed consent must be clear and concise, comprehensible, and free from bias. The patient must consent without coercion. Information regarding the potential risk in the medical intervention must be complete, and subsequently, the physician must abide by the Clinical Practice Guidelines and the protocols of professional action modes approved by the scientific community. Conclusion: The medical record, with its objective and subjective components, informed consent, and the lex artis are determining factors for assessing objective imputation in reckless offenses and evaluating criminal liability.
Keywords: Informed Consent; Lex artis; Objective Imputation